2014
DOI: 10.1093/hmg/ddu411
|View full text |Cite
|
Sign up to set email alerts
|

FTO genetic variants, dietary intake and body mass index: insights from 177 330 individuals

Abstract: FTO is the strongest known genetic susceptibility locus for obesity. Experimental studies in animals suggest the potential roles of FTO in regulating food intake. The interactive relation among FTO variants, dietary intake and body mass index (BMI) is complex and results from previous often small-scale studies in humans are highly inconsistent. We performed large-scale analyses based on data from 177,330 adults (154 439 Whites, 5776 African Americans and 17 115 Asians) from 40 studies to examine: (i) the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
4
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(142 citation statements)
references
References 52 publications
9
119
4
10
Order By: Relevance
“…This study further showed that a lower protein intake attenuated the effect of FTO on BMI [10]. Another large-scale analyses (177,330 adults) showed a positive association of FTO variant with dietary protein intake [11]. Common MC4R variants have mostly been related to eating behavior [12].…”
Section: Accepted Manuscriptsupporting
confidence: 51%
“…This study further showed that a lower protein intake attenuated the effect of FTO on BMI [10]. Another large-scale analyses (177,330 adults) showed a positive association of FTO variant with dietary protein intake [11]. Common MC4R variants have mostly been related to eating behavior [12].…”
Section: Accepted Manuscriptsupporting
confidence: 51%
“…When adults were in a low-protein dietary state, brain response in the inferior orbitofrontal cortex (implicated in emotion and reward-driven decision-making) was higher for savory food odor and visual cues relative to a control condition, and the participants also exhibited a higher preference for savory foods (Griffioen-Roose et al, 2014). Additionally, another study found a relationship between a polymorphism in the FTO gene, which has been associated with body mass index and obesity risk, and greater total energy and protein intake, but lower carbohydrate intake (Qi et al, 2014). Similar findings were reported in a subsample of children and adolescents (Qi et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…FTO expression in the hypothalamus is regulated by feeding, fasting, and energy restriction (67)(68)(69)(70)(71)(72)(73). Both animal and human studies support the association between FTO and food intake (9,10,74), and FTO also has been linked to habitual appetitive behaviors (11,12) and appetite-related hormones (ghrelin and leptin) (75,76). Moreover, a recent study reported that the obesity-predisposing allele of the FTO variant was associated with a reduction in food cravings and appetite during an intervention with hypocaloric weight-loss diets (44).…”
Section: Discussionmentioning
confidence: 96%
“…Given its strong effect on obesity and possible biological function in regulating energy balance (8), there is great interest in the fat mass and obesity-associated (FTO) gene. Recent large-scale analyses found that the obesity-risk allele (A allele) of the FTO variant is associated with increased food intake (9,10), and previous studies also reported that the FTO obesity-risk allele was associated with a reduced response in hunger and satiety after the meal in adults and children (11,12). A number of studies have examined whether diet/lifestyleinduced weight loss differs between the FTO genotype groups (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%